Differences in muscular power of lower extremities in young female athletes - Rousanoglou, E.; Nikolaidou, M. E.; Plessa, E.; Nioti, P.; Konstantinos, B. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of this study was to investigate possible differences in mechanical parameters in reliable jumping tests when these were performed by young female athletes of different training groups. The results show that the individuation of abilities is developed rather early, shaping the frame of sports orientation.